Criterion validity of performance tests and physiological characteristics in elite cross-country skiers - Bucher, E.; Wehrlin, J. P.; Millet, G. P.; Steiner, T. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Performance testing is an integral component of the training process for elite cross-country skiers. The performance determinants should demonstrate high criterion validity and reflect the physiological demands of on-snow competitions. This study investigated the validity of three aerobic-based laboratory performance tests utilized by Swiss national team athletes.